Raptor Code for Energy-Efficient Wireless Body Area Network Data Transmission - Lydia Sari; Antonius Aditya (Universitas Ahmad Dahlan, 2015)
Wireless Body Area Network (WBAN) is a device developed mainly for the purpose of monitoring the medical condition of a human. WBAN is worn on the surface or in the human body, and it contains a wireless communication device. A WBAN device is required to be small-sized, with limited power and high data reliability. The data reliability can be obtained by using a carefully designed channel coding scheme so that the energy consumed can be maintained at a low level. In this paper, data transmission in Rayleigh, Rician, and Nakagami-m fading channels using Raptor and BCH codes is simulated. Simulation results show that Raptor-coded data transmission consumes lower energy compared to BCH-coded transmission for various fading channels if the transmission distance exceeds 10 meters. Therefore, Raptor code is a good candidate for the channel coding scheme for WBAN.